Sustaining maize (Zea mays) productivity through improved agronomic management practices under jhum ecosystems - I, RAMKRUSHNA G; LAYEK, JAYANTA; DAS, ANUP; VERMA, B C; PANDE, RACHNA; MOHAPATRA, K P; BABU, SUBHASH (The Indian Journal of Agricultural Sciences, 2023)
Maize (Zea mays L.) is an important crop cultivated in jhum farming (shifting cultivation) practiced in north-east India. However, productivity of maize in jhum is very low due to use of local cultivars and poor management practices. A participatory field trial was conducted in 2015–16 and 2016–17 to assess the impact of high yielding varieties/ cultivars and improved management practices on maize productivity and soil fertility in farmer’s jhum field of Ri- Bhoi District, Meghalaya. Nine cultivars/varieties of maize (Improved cultivars/varieties: Hemant, Vijay Composite, Megha Maize 1, Megha Maize 2, RCM 1-1, RCM 1-3, RCM 75 and local cultivars: SaruTangring and SaruBhoi) were evaluated under improved agronomic management practices (IAMP) and farmers’ practice in a factorial randomized block design. Results revealed that number of seeds per cob, seed weight per cob and seed index were significantly higher under IAMP compared to that of farmers’ practice during both the years. The IAMP produced significantly higher grain and stover yields of maize than farmers’ practice. The maize variety Megha Maize 1 recorded significantly higher grain yield (3.15 and 2.92 t/ha in 2015–16 and 2016–17, respectively) than the rest of varieties/cultivars. The variety RCM 75 (7.13 t/ha) being at par with Megha maize 1 (6.83 t/ha) produced higher stover yield than others in year 2015–16. IAMP recorded significantly higher soil organic carbon, pH and available N, P, K over farmers’ practice after two years. Thus, the study recommends adoption of improved agronomic management practices and high yielding cultivars like Megha Maize 1 and RCM 75 for sustaining soil fertility and enhancing productivity of maize under jhum farming in the north eastern region (NER) of India.